Analysis of sentence 3681-17: The Constitutional Court faced with the dual criminal prosecution system in force in Chile - Boys Loeb, Henry (Derecho Público Iberoamericano, 2021)
In a paradigmatic ruling, the Constitutional Court accepted what it considered to be the Inter-American standard with respect to the publicity of criminal proceedings, addressing, in passing, a problem of extreme relevance in Chile: the coexistence of two systems of criminal prosecution and their different standards with respect to the guarantee of the fundamental rights of those subject to the process. However, in doing so, it gave rise to well-founded doubts as to whether or not it exceeded its powers. Far from providing clarity on the matter, it contradicted its already established jurisprudence regarding the normative rank of international treaties in the Chilean legal system. In this paper we study the two possible readings of the judgment and the problems of material justice that both raise.